International Investment Agreements, Human Rights, and the Path to Net-Zero: What Role for Corporate Codes? - Susan L. Karamanian (22329931) (2025)
The Paris Agreement’s commitment to achieve net-zero greenhouse gas emissions by 2050 has resulted in an uptick in environmental laws and regulations. However, such state conduct could implicate other legal obligations and norms, including international investment law and international human rights law. The conversation about human rights, net-zero and investment treaties, including arbitration cases and arbitral awards under the treaties, is in its relative infancy. This article examines how investment treaties are equipped to reconcile relevant norms with a particular focus on corporate codes and policies that pronounce broad commitments to protecting human rights and the environment. It establishes certain principles to guide parties and arbitral tribunals as to the codes while recognizing the inevitable challenges they will face. Other Information Published in: Business and Human Rights Journal License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1017/bhj.2024.31